Pushing the Limits in a Modified Nordic Test System with High Penetration of Renewable Energy Sources - Scheiner, Elisabeth; Burlakin, Ilya; Kuri, Ananya; Mehlmann, Gert; Luther, Matthias (IET Conference Proceedings, 2024)
The loss of voltage stability due to the continuous expansion of renewable energy sources (RES) in the system may lead to an increased risk of power outages. This paper examines how the shift to inverter-dominated power systems affects voltage stability requirements. Using the well-known Nordic Test System, modifications were made to increase the share of RES in the total installed capacity from 0% to 35% and 50%. Various key performance indicators (KPIs) are used to analyze and compare the different RES expansion scenarios. A dynamic system analysis has been carried out and evaluated the test systems with different proportions of RES concerning the effects on voltage stability. Countermeasures are proposed utilizing additional reactive power sources as Static Synchronous Compensators (STATCOMs) devices to overcome the emerging stability issues.
CRIS-Team Scopus Importer:2026-01-26
Keywords: DYNAMIC REACTIVE POWER COMPENSATION; GRID-FOLLOWING INVERTERS; INVERTER-BASED GENERATION; NORDIC TEST SYSTEM; VOLTAGE STABILITY